Implementation of double Feynman gate in high dimensional quantum systems - Zhu, Yanbing; Shang, Jiaqi; Fan, Ya-nan; Kou, Yunjie; Qu, Xiaofei; Yan, Xiang-an; Zhang, Yunjie; Wang, Feiran (Scientific reports, 2025)
The photonic platform has emerged as a preferred choice for quantum computing and information processing due to its low loss and high integration capabilities. In the present research, we propose a high-dimensional double Feynman gate utilizing single-photon hybrid degrees of freedom coding. This gate can manipulate two qubits simultaneously, demonstrating effective quantum state conversion. Our experimental design offers valuable insights for the investigation of high-dimensional optical quantum logic gates and advances quantum fundamental research.